2023
DOI: 10.3390/foods12152951
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Profiling of Metabolites and Volatile Organic Compounds in Citrus depressa Hayata Fruits from Kagoshima, Okinawa, and Taiwan

Abstract: Citrus depressa Hayata is a small-fruit citrus species; it is indigenous to Kagoshima, Okinawa, and Taiwan. The metabolites and volatile organic compounds (VOCs) that affect the flavor of its fruits have not been investigated based on geographical origin. In the present study, we investigated the metabolite and VOC profiles of 18 C. depressa cultivation lines from these regions. Multivariate analysis revealed differences in the metabolites of C. depressa based on its cultivation origins; variations in sugar, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…By combining HS-GC–IMS and UPLC–Q-TOF-MS we can more comprehensively elucidate the differences in the chemical compositions of samples and the factors affecting them. The cultivation system and the origin of citrus cultivars affect their metabolites and volatile organic compounds, which may ultimately influence their flavor quality ( Asikin et al, 2023 ; Pieracci et al, 2022 ). Agricultural scientists have bred a wide variety of citrus hybrids in the pursuit of excellent properties, such as high sugar and low acidity, tenderness and low dregs, easy peeling, rich nutritional value, high yield, and easy management.…”
Section: Introductionmentioning
confidence: 99%
“…By combining HS-GC–IMS and UPLC–Q-TOF-MS we can more comprehensively elucidate the differences in the chemical compositions of samples and the factors affecting them. The cultivation system and the origin of citrus cultivars affect their metabolites and volatile organic compounds, which may ultimately influence their flavor quality ( Asikin et al, 2023 ; Pieracci et al, 2022 ). Agricultural scientists have bred a wide variety of citrus hybrids in the pursuit of excellent properties, such as high sugar and low acidity, tenderness and low dregs, easy peeling, rich nutritional value, high yield, and easy management.…”
Section: Introductionmentioning
confidence: 99%
“…Chenpi extract contains flavonoids such as narirutin, hesperidin, nobiletin, tangeretin, and 5-demethylnobiletin, which show antioxidant, anti-inflammatory, and anti-obesity effects [ 12 , 13 ]. Citrus depressa Hayata is a small citrus known as hirami lemon, flat lemon, thin-skinned flat lemon, and is distributed in Japan and Taiwan [ 14 ]. Research has shown that the ethanol or methanol extract of the peel of C. depressa contains polymethoxylated flavonoids such as nobiletin, tangeretin, sinensetin, and 5-demethylnobiletin, which showed inhibitory effects on lipid accumulation in the liver and adipose tissue [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%